Putting Practice into Theory: Reconciling Academic Discourse with Experience - Bounds, Michael; Phibbs, Peter (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment); Vol 4 No 1 (2017): April 2017DO - 10.24843/JRS.2017.v04.i01.p07, 2017)
This paper is based on our work with experienced professionals in the Practitioner in Residence (PIR) Program. The program allows an experienced urban practitioner to undertake a period of supported research in residence at the University of Sydney under the auspices of the Henry Halloran Trust. The aim is to enable professionals to impart their knowledge to other urban professionals and thereby inform their practice. The PIR writes from experience on a topic of concern, relating it to the literature in the field and arguing the case for change. Our PIRs bring experience to the project and, under guidance derive a principle/s that can speak to other practitioners in a well researched and grounded argument. Outside the institutional constraint of their office PIRs are able to bring the wisdom of experience to discussing the politics and pragmatics that contend with planning goals. The program is part of a broader Trust agenda to better connect Australian urban planning practice to the evidence base within urban planning research. Through the program we hope to produce research outputs relevant and accessible to practitioners. The paper discusses the dynamics of the PIR program, the necessary links between theory and practice and the problems of relevance and accessibility of planning research. Keywords: action research, research led practice